2021
DOI: 10.1055/s-0041-1725128
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Robot-Assisted Gait Training on Functional Skills in Children with Cerebral Palsy

Abstract: This study was aimed to investigate the effects of robot-assisted gait training (RAGT) on motor functions, spasticity status, balance, and functionality in children with cerebral palsy (CP). A total of 26 patients who were diagnosed with CP (diplegic, with gross motor function classification system [GMFCS] levels of 2–5) and who regularly participated in a rehabilitation program were recruited in the study after obtaining approval from their parents. The patients were randomly assigned to two groups. Group 1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…277 studies were excluded as irrelevant. Finally, 43 studies that did not meet the inclusion criteria of PICOS were excluded and the final seven studies were selected ( Drużbicki et al, 2013 ; Fu et al, 2022 ; Moll et al, 2022 ; Pool et al, 2021 ; Sarhan et al, 2014 ; Wallard et al, 2017 ; Yaşar et al, 2022 ) ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…277 studies were excluded as irrelevant. Finally, 43 studies that did not meet the inclusion criteria of PICOS were excluded and the final seven studies were selected ( Drużbicki et al, 2013 ; Fu et al, 2022 ; Moll et al, 2022 ; Pool et al, 2021 ; Sarhan et al, 2014 ; Wallard et al, 2017 ; Yaşar et al, 2022 ) ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 11 assessment items, items 2 through 11 were assessed, with the exception of item 1, which assesses external validity. The results showed that two articles ( Drużbicki et al, 2013 ; Moll et al, 2022 ) were rated as fair and five articles ( Fu et al, 2022 ; Pool et al, 2021 ; Sarhan et al, 2014 ; Wallard et al, 2017 ; Yaşar et al, 2022 ) were rated as good ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The advent and advancement of robotics have enabled the development of tasks that humans cannot perform, or at least not with such precision [66][67][68]. In the field of eHealth, robotics has played a fundamental role in helping and treating people with various neurological conditions such as trauma [69], dementia [33][34][35][36][37], ASD [24][25][26][27][28], cerebral palsy [29][30][31][32] and ADHD [18][19][20][21][22][23]. Although in recent years the application of robotics in the treatment and support of ADHD has received considerable research attention, however, it is far inferior compared to dementia, autism, and cerebral palsy.…”
Section: Evolution Of Robotic Application In Adhd Treatmentmentioning
confidence: 99%
“…Several NDD treatments have significantly harnessed the potential of robotics. The use of robots in the treatment of autism spectrum disorder (ASD) [24][25][26][27][28], cerebral palsy [29][30][31][32] and dementia [33][34][35][36][37] has produced good results and established the basis for applying their developments in the treatment of ADHD. However, its application in the field of ADHD has been much less, representing 1.1% -1.8% compared to other NND.…”
Section: Introductionmentioning
confidence: 99%
“…The robotic systems that were used in the articles that were included in this systematic review mainly focused on gait parameters and lower limb motor dysfunctions. The most commonly used were the Lokomat system [27][28][29]32], followed by the Innowalk Pro [30], the Walkbot-K system [31] and Robogait [33]. All sessions were individualized and included between 20 [31] and 52 [27] children who were diagnosed with cerebral palsy.…”
Section: Robotic Systemsmentioning
confidence: 99%